Parodi “Perjamuan Terakhir” Olimpiade Paris Sebagai Produk Kontradiktif Postmodern terhadap Nilai Kristiani - Yustinus, Yustinus; Sirait, Hikman; Romika, Romika (Ritornera - Jurnal Teologi Pentakosta Indonesia, 2024)
AbstractThis study aims to discuss the parody of "The Last Supper" presented during the opening of the 2024 Paris Olympics as a contradictory product of postmodern values against Christian values. This research employs a qualitative method through literature review. The method not only focuses on collecting data but also aims to deeply analyze the identified sources so that each piece of data can provide arguments that either support or refute the main analysis. The study explores the value conflicts arising between the original meaning of The Last Supper in Matthew 26:17-29 and its reinterpretation in modern culture. The findings reveal that the narrative of The Last Supper in the Gospel carries several significant messages or meanings, which give rise to spiritual values as part of God's covenant with His people. The first meaning is that Jesus' Last Supper serves as a reminder of God's promise to reunite with His people at the Lamb's Supper in Heaven. The second meaning is the value of liberation. The third meaning highlights the understanding that the disciples are part of the same body of Christ. The fourth meaning is the fellowship value (1 Corinthians 10:16b). The fifth meaning pertains to sanctification, where the wine shared by Jesus symbolizes His blood shed for all humanity. The sixth meaning emphasizes gratitude, as The Last Supper embodies a practice of thanksgiving. The seventh meaning views The Last Supper as a sacred liturgy. The eighth meaning focuses on evangelism. The ninth meaning reflects the extraordinary value of Jesus' total surrender. Finally, the tenth meaning represents The Last Supper as a symbol of the New Covenant. In conclusion, understanding the profound and sacred values of The Last Supper opens the eyes of Christians to the immense love and grace of God for humanity. These values should inspire Christians to remain steadfast and grow stronger in their faith in Christ.AbstrakPenelitian ini bertujuan untuk membahas parodi “Perjamuan Terakhir” yang ditampilkan dalam pembukaan Olimpiade Paris 2024 sebagai produk kontradiktif nilai-nilai postmodern terhadap nilai-nilai Kristiani. Penelitian ini menggunakan metode kualitatif melalui studi literatur. Metode ini tidak hanya berfokus pada pengumpulan data, tetapi juga bertujuan untuk menganalisis secara mendalam sumber-sumber yang diidentifikasi, sehingga setiap data yang diperoleh dapat memberikan argumen yang mendukung atau menampik analisis utama.  Penelitian ini mengeksplorasi konflik nilai yang muncul antara makna asli Perjamuan Terakhir dalam Matius 26:17-29 dengan interpretasi budaya modern. Hasil penelitian yaitu narasi Perjamuan Terakhir di Injil mengandung beberapa makna atau pesan penting yang melahirkan nilai-nilai spiritual sebagai bagian dari janji Allah bagi umat-Nya. Makna pertama, Perjamuan Terakhir Yesus sebagai pengingat akan janji Allah untuk berkumpul bersama Tuhan kembali dalam Perjamuan Anak Domba Allah di Surga, Makna kedua adalah makna pembebasan, makna ketiga memberi pemahaman bahwa para murid adalah bagian dari satu tubuh Kristus yang sama. Makna keempat, Perjamuan Tuhan memiliki makna persekutuan (1 Kor 10:16b). Makna kelima, yakni nilai pengudusan. Anggur yang Yesus bagikan adalah simbol darah-Nya yang tercurah bagi semua umat manusia. Makna keenam, Perjamuan Terakhir sebagai praktik pengucapan syukur. Makna ketujuh, Perjamuan Terakhir sebagai liturgi sakral. Makna kedelapan, adalah makna penginjilan. Makna kesembilan adalah nilai penyerahan total Yesus yang luar biasa. Makna kesepuluh, Perjamuan Terakhir sebagai simbol Perjanjian Baru. Kesimpulan Pemahaman akan makna Perjamuan Terakhir yang mengandung nilai-nilai suci dan mulia membuka mata umat Kristen akan besarnya kasih dan anugerah Tuhan bagi manusia. Nilai-nilai yang selayaknya membuat umat Kristen bertahan bahkan semakin kuat dengan imannya kepada Kristus.